MITOS SEKSUALITAS DALAM IKLAN - Jemmy Junius Pah (Nyimak: Journal of Communication, 2018)
ABSTRAK Penelitian ini bertujuan untuk membongkar mitos seksualitas pada iklan cetak LYNX versi The Cleaner You Are The Dirtier You Get yang hanya menampilkan sosok model wanita seksi tanpa menyertakan model lakilaki. Penelitian ini merupakan penelitian kualitatif. Metode analisis semiotika Roland Barthes digunakan untuk mengetahui makna dari tanda-tanda yang ada pada iklan dan ideologi yang tersembunyi di balik iklan. Setelah menganalisis iklan LYNX versi The Cleaner You Are The Dirtier You Get, peneliti menemukan mitos seksualitas pada berbagai rangkaian penanda (signifier) dan petanda (signified) pada iklan. Penggunaan ikon-ikon seksualitas, seperti model wanita seksi, memperlihatkan adanya eksploitasi terhadap perempuan baik secara fisik maupun nonfisik. Adapun ideologi yang tersembunyi di balik iklan ini adalah konsumerisme, patriarkal, dan kapitalisme.Kata Kunci: Mitos seksualitas, iklan, semiotika, kapitalisme, konsumerisme, patriarkalThis study aimed to dismantle the myth of sexuality in print advertising LYNX version of The Cleaner You Are The dirtier You Get. The objects of this study were LYNX print ads version of The Cleaner You Are The dirtier You Get that displays only the female sexy model figure without including the male model. This study used a qualitative research methodology. The method of Roland Barthes' semiotic analysis is used to determine the meaning of the signs that exist on the stored advertisements and also the ideology behind the ad. After observing the LYNX print ads version of The Cleaner You Are The dirtier You Get, researchers found the myth of sexuality in various signifier and the signified that exist in the ad. The use of icons such as sexuality sexy female models showed their exploitation efforts both physical and non-physical by exploiting women's bodies and desires. The ideology that is hidden behind LYNX print ads version of The Cleaner You Are The dirtier You Get is the ideology of consumerism, patriarchy and capitalism. Associated with the research, the authors would like to suggest that the ad makers and manufacturers are not continuously use women's bodies as 'material' advertising, especially if the woman is only used as mere sex objects.Keyword: Myth Sexuality, LYNX Print Ad, Semiotics, Roland Barthes, Consumerism, Patriarchy, Kapitalism